Efficacy and gastrointestinal tolerability of methotrexate in late-onset rheumatoid arthritis patients: a prospective cohort study - Esra Dilsat Bayrak; Ilknur Aktas (Egyptian Rheumatology and Rehabilitation, 2023)
Abstract Background The proportion of the late-onset forms of disease is growing in rheumatoid arthritis (RA) population. Concerns about comorbidities and drug adverse events lead to delay or ineffective treatment in these patients. The aim of this study is to analyze the tolerability and efficacy of methotrexate therapy in late-onset RA (LORA) patients and compare the baseline characteristics, efficacy, and gastrointestinal (GIT) adverse effects of methotrexate treatment between LORA and young-onset RA patients (YORA). Results Patients whose symptoms began after 65 years or older were classified as LORA. Baseline characteristics, rheumatoid factor (RF) and anti-citrullinated protein antibody (ACPA) status, C-reactive proten (CRP) levels, disease activity scores, and radiographs of hands and feet were recorded. Patients were started to methotrexate therapy and followed for 6 months. Female gender was predominant in both LORA and YORA. LORA patients had less seropositivity (RF or anti-CCP), higher CRP levels, and higher DAS 28 scores. More than half of the patients (58%) had large joint involvement. Remission rates were higher in LORA patients, and total remission and low disease activity rates were similar. Methotrexate withdrawal due to gastrointestinal adverse events (nausea and vomiting) was lower than YORA patients. Logistic regression analysis demonstrated that DAS 28 score was the only predictor for disease remission (p: 0.000), and no predictive factor was found for methotrexate-related adverse events. Conclusion Methotrexate-related gastrointestinal adverse events do not increase in LORA patients, and nausea-vomiting is seen lower than YORA. Methotrexate is well tolerated and effective in LORA patients, and a large amount of patients achieve treatment targets after 6 months of treatment with MTX. Methotrexate should be started immediately in LORA without additional concerns on adverse effects.